Before she was found - Gudenkauf, Heather (Park Row Books, 2019)
For twelve-year-old Cora Landry and her friends Violet and Jordyn, it was supposed to be an ordinary sleepover--movies and Ouija and talking about boys. But when they decide to sneak out to go to the abandoned rail yard on the outskirts of town, little do they know that their innocent games will have dangerous consequences.